System of Complex Equations

Algebra Level 3

x , y x, y and z z are complex numbers that satisfy the equations x + y + z = 2 x+y+z = 2 , x y + y z + z x = 3 xy + yz + zx = 3 and x y z = 4 xyz =4 . Given that 1 1 x y z + 1 1 y z x + 1 1 z x y = a b \frac {1}{1-x-yz} + \frac {1}{1-y-zx} + \frac {1}{1-z-xy} = \frac {a}{b} , where a a and b b are coprime positive integers, what is the value of a + b a+b ?


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

13 solutions

Ryandk St
May 20, 2014

First, let's do some research in 1 x y z 1-x-yz . Since x + y + z = 2 x+y+z=2 ,so 1 x = 2 x 1 = y + z 1 1-x=2-x-1=y+z-1 . then 1 x y z = y + z 1 y z = ( y 1 ) ( z 1 ) 1-x-yz=y+z-1-yz=-(y-1)(z-1) ,do the same to 1 y z x 1-y-zx and 1 z x y 1-z-xy . Thus, the expression, is ( 1 ( x 1 ) ( y 1 ) + 1 ( x 1 ) ( z 1 ) + 1 ( y 1 ) ( z 1 ) ) = ( z 1 ) + ( y 1 ) + ( x 1 ) ( x 1 ) ( y 1 ) ( z 1 ) -(\frac{1}{(x-1)(y-1)}+\frac{1}{(x-1)(z-1)}+\frac{1}{(y-1)(z-1)}) = - \frac { (z-1)+(y-1)+(x-1)}{(x-1)(y-1)(z-1)} .

The numerator is ( z 1 ) + ( y 1 ) + ( x 1 ) = x + y + z 3 = 1 (z-1)+(y-1)+(x-1)=x+y+z-3=-1 . As for the denominator, expanding ( x 1 ) ( y 1 ) ( z 1 ) = x y z x y x z y z + x + y + z 1 = 4 3 + 2 1 = 2 (x-1)(y-1)(z-1) = xyz-xy-xz-yz+x+y+z-1 =4-3+2-1=2 . Hence, the expression equals 1 2 \frac {1}{2} , so the answer is 1 + 2 = 3 1+2=3 .

The key insight is realizing that 1 x y z = ( y 1 ) ( z 1 ) 1-x-yz=-(y-1)(z-1) , which motivates work done on this problem.

Calvin Lin Staff - 7 years ago
Anup Raj
May 20, 2014

It has been given:

x + y + z = 2. x + y + z = 2.

Rearranging,

y + z 1 = 1 x ; z + x 1 = 1 y ; x + y 1 = 1 z ; y + z - 1 = 1 - x ; z + x - 1 = 1 - y ; x + y - 1 = 1 - z ;

Therefore, denominator of given fraction changes as:

1 x y z = y + z 1 y z = ( y 1 ) ( z 1 ) ; 1 - x - yz = y + z -1 - yz = - ( y - 1 ) \cdot ( z - 1 ) ;

1 y z x = z + x 1 z x = ( z 1 ) ( x 1 ) ; 1 - y - zx = z + x -1 - zx = - ( z - 1 ) \cdot ( x - 1 ) ;

1 z x y = x + y 1 x y = ( x 1 ) ( y 1 ) ; 1 - z - xy = x + y -1 - xy = - ( x - 1 ) \cdot ( y - 1 ) ;

Hence, the given fraction becomes

1 ( y 1 ) ( z 1 ) + 1 ( z 1 ) ( x 1 ) + 1 ( x 1 ) ( y 1 ) = ( x 1 ) ( y 1 ) ( z 1 ) ( x 1 ) ( y 1 ) ( z 1 ) = ( x + y + z 3 ) x y z + y + z + x x y y z z x 1 = 1 4 + 2 3 1 = 1 2 \begin{aligned} & \frac {- 1}{( y - 1 ) \cdot ( z - 1 )} + \frac {- 1}{( z - 1 ) \cdot ( x - 1 )} + \frac {- 1}{( x - 1 ) \cdot ( y - 1 )} \\ = & \frac {- ( x - 1 ) - ( y - 1 ) - ( z - 1 )}{( x - 1 ) \cdot ( y - 1 ) \cdot ( z - 1 )} \\ = & \frac {- ( x + y + z - 3 )}{ xyz + y + z + x - xy - yz - zx -1} \\ = & \frac {1}{4 + 2 - 3 - 1} = \frac {1}{2} \end{aligned}

which is of the form a b \frac {a}{b} . So, a = 1 and b = 2 , a + b = 3. \Rightarrow, a + b = 3.

[Latex Edits]

Most correct solutions consist of a series of substitutions and simplifications. This solution is symmetric, that makes it relatively simple, but there are many correct non-symmetric, solutions.

Even though one can find the numbers x,y,z approximately, using a computer or an advanced calculator, this cannot possibly be used to obtain a correct solution.

Calvin Lin Staff - 7 years ago
Anand Deshmane
May 20, 2014

First of all let us establish some equations that are going to be useful to us
Number 1: 1 x = y + z 1 ; 1 y = x + z 1 ; 1 z = x + y 1 1-x=y+z-1 ; 1-y=x+z-1 ; 1-z=x+y-1 Number 2: ( x 1 ) ( y 1 ) ( z 1 ) = x y z x y y z x z + x + y + z 1 = 2 (x-1)*(y-1)*(z-1)= xyz-xy-yz-xz+x+y+z-1 = 2

Note that by using the equation Number 1 , the expression 1 1 x y z + 1 1 y x z + 1 1 z x y \frac {1}{1-x-yz} + \frac {1}{1-y-xz} + \frac{1}{1-z-xy} becomes 1 ( y 1 ) ( 1 z ) + 1 ( z 1 ) ( 1 x ) + 1 ( x 1 ) ( 1 y ) \\ \frac {1}{(y-1)*(1-z)} + \frac {1}{(z-1)*(1-x)} + \frac{1}{(x-1)*(1-y)}

\\ Now let us simplify the first two terms. \\ 1 1 x y z + 1 1 y x z = 1 ( y 1 ) ( 1 z ) + 1 ( z 1 ) ( 1 x ) \normalsize \frac {1}{1-x-yz} + \frac {1}{1-y-xz} = \frac {1}{(y-1)*(1-z)} + \frac {1}{(z-1)*(1-x)} = ( z 1 ) ( 2 x y ) ( x 1 ) ( y q ) ( z 1 ) ( z 1 ) = ( z 1 ) ( z ) 2 ( z 1 ) = z 2 \\ = \large \frac{(z-1)*(2-x-y)}{(x-1)*(y-q)*(z-1)*(z-1)} = \frac{(z-1)*(z)}{2*(z-1)} = \frac{z}{2}

Now all we have to find out is z 2 + 1 ( x 1 ) ( 1 y ) \frac{z}{2} + \frac{1}{(x-1)(1-y)}

Using equation Number 2 ( x 1 ) ( 1 y ) = 2 ( z 1 ) (x-1)(1-y) = \frac {-2}{(z-1)}

Therefore z 2 + 1 ( x 1 ) ( 1 y ) = z 2 + 1 2 z 1 = z 2 ( z 1 ) 2 = 1 2 = a b \normalsize \frac{z}{2}+\frac{1}{(x-1)*(1-y)} = \frac{z}{2} + \frac{1}{\frac{-2}{z-1}} \\ \normalsize = \frac{z}{2} - \frac{(z-1)}{2} = \frac {1}{2} = \frac {a}{b}

Therefore a + b = 3 \large a+b=\boxed 3

Alan Chee
May 20, 2014

After simplifying the expression, we get

1 1 x y z + 1 1 y z x + 1 1 z x y = \frac{1}{1-x-yz} + \frac{1}{1-y-zx} + \frac{1}{1-z-xy} = ( x 2 y z + x 2 y + x 2 z + x y 2 z + x y 2 + x y z 2 x y + x z 2 x z 2 x + y 2 z + y z 2 y z 2 y 2 z + 3 ) ( ( x y + z 1 ) ( x z + y 1 ) ( x + y z 1 ) ) \frac{-(x^2 y z+x^2 y+x^2 z+x y^2 z+x y^2+x y z^2-x y+x z^2-x z-2 x+y^2 z+y z^2-y z-2 y-2 z+3)}{((x y+z-1) (x z+y-1) (x+y z-1))}

Then we just use the given conditions, and we get 1 2 \frac{1}{2} as the value of the expression. Hence, we get a + b = 1 + 2 = 3 a + b = 1 + 2 = 3

Kee Wei Lee
May 20, 2014

Now as x + y + z = 2 x+y+z=2 implies 1 x = y + z 1 1-x=y+z-1

So 1 x y z = 1 + y + z z y = ( y 1 ) ( z 1 ) 1-x-yz=-1+y+z-zy=-(y-1)(z-1)

So similarly,

1 y z x = ( x 1 ) ( z 1 ) 1-y-zx=-(x-1)(z-1) and 1 z x y = ( x 1 ) ( y 1 ) 1-z-xy=-(x-1)(y-1)

Consider the polynomial f ( a ) = a 3 2 a 2 + 3 a 4 f(a)=a^3-2a^2+3a-4 where it have roots x , y , z x,y,z by Vieta's Theorem.

Now consider the polynomial;

f ( a ) = ( ( a + 1 ) 3 2 ( a + 1 ) 2 + 3 ( a + 1 ) 4 f(a)=((a+1)^3-2(a+1)^2+3(a+1)-4 = a 3 + a 2 + 2 a 2 =a^3+a^2+2a-2

At which will have roots x 1 , y 1 , z 1 x-1,y-1,z-1

So we know from here by Vieta's Theorem that;

( x 1 ) ( y 1 ) ( z 1 ) = 2 (x-1)(y-1)(z-1)=2 implying

2 ( y 1 ) ( z 1 ) = x 1 \frac{2}{(y-1)(z-1)}=x-1

2 ( x 1 ) ( z 1 ) = y 1 \frac{2}{(x-1)(z-1)}=y-1

2 ( x 1 ) ( y 1 ) = z 1 \frac{2}{(x-1)(y-1)}=z-1

Hence;

1 1 x y z + 1 1 y z x + 1 1 z x y = \frac{1}{1-x-yz}+\frac{1}{1-y-zx}+\frac{1}{1-z-xy}=

( 1 ) ( 1 ( y 1 ) ( z 1 ) + 1 ( x 1 ) ( z 1 ) + 1 ( x 1 ) ( y 1 ) ) (-1)(\frac{1}{(y-1)(z-1)}+\frac{1}{(x-1)(z-1)}+\frac{1}{(x-1)(y-1)})

= ( 1 ) ( 1 2 ) ( x 1 + y 1 + z 1 ) =(-1)(\frac{1}{2})(x-1+y-1+z-1)

= ( 1 ) ( 1 2 ) ( x + y + z 3 ) =(-1)(\frac{1}{2})(x+y+z-3)

= ( 1 ) ( 1 2 ) ( 2 3 ) = 1 2 =(-1)(\frac{1}{2})(2-3)=\frac{1}{2}

Therefore our require value is 1 + 2 = 3 1+2=3

Kevin Li
May 20, 2014

First we notice that x , y , z x, y, z are roots of the cubic equation A 3 2 A 2 + 3 A 4 = 0 A^3-2A^2+3A-4=0 by Vieta's Theorem. Now we try to manipulate the algebraic expression on the left hand side so that each denominator contains only expressions of one variable, so it would be easier for us to apply the equation we have just obtained. Notice that since y z = 3 x y z x = 3 x ( y + z ) = 3 x ( 2 x ) = x 2 2 x + 3 yz=3-xy-zx=3-x(y+z)=3-x(2-x)=x^2-2x+3 we can cancel out y , z y, z 1 1 x y z = 1 1 x ( x 2 2 x + 3 ) = 1 x 2 + x 2 \frac{1}{1-x-yz}=\frac{1}{1-x-(x^2-2x+3)}=\frac{1}{-x^2+x-2} . Then since x 3 2 x 2 + 3 x 4 = 0 x^3-2x^2+3x-4=0 we long divide it by the denominator, 0 = x 3 3 x 2 + 3 x 4 = ( x 2 + x 2 ) ( x + 1 ) 2 0=x^3-3x^2+3x-4=(-x^2+x-2)(-x+1)-2 so x 2 + x 2 = 2 x + 1 -x^2+x-2=\frac{2}{-x+1} Now 1 1 x y z = x + 1 2 \frac{1}{1-x-yz}=\frac{-x+1}{2} (Here we assumed x 1 x\neq 1 . In fact, if x = 1 x=1 , we would have y + z = 1 y+z=1 , y z = 4 yz=4 , y + z + y z = 3 y+z+yz=3 , adding up the first two equations and comparing with the third would give us a contradiction.)

So the left hand side would be equal to 1 x 2 + 1 y 2 + 1 z 2 = 3 2 x + y + z 2 = 1 2 \frac{1-x}{2}+\frac{1-y}{2}+\frac{1-z}{2}=\frac32-\frac{x+y+z}{2}=\frac12

Thus the answer is 1 + 2 = 3 1+2=\boxed{3} .

x+y+z=2,xy+yz+zx=3,xyz=4, (x+y+z)^2=X2+y2+z2+2(xy+yz+zx), x2+y2+z2=-2, x^3 + y^3 + z^3 - 3xyz = (x+y+z) (x^2 + y^2 + z^2 - xy - yz - xz), x^3 + y^3 + z^3=2, (x + y + z) 3 = x3 + y3+ z3+ 3z2x + 3x2z + 3yz2 + 3zy2 + 3x2y + 3xy2 + 6xyz, z2x + x2z + yz2 + zy2 + x2y + xy2=-6, 1/(1−x−yz)+1/(1−y−zx)+1/(1−z−xy)=a/b, After taking lcm , (1−y−zx)(1−z−xy)+(1−x−yz)(1−z−xy)+(1−x−yz)(1−y−zx)/(1−x−yz)(1−y−zx)(1−z−xy) =a/b, simplifying and substituting the above find values we get, -2/-4=a/b=1/2, a=1,b=2, a+b=3

Jeffrey Robles
May 20, 2014

Since x+y+z=2, then -x=y+z-2. Then, 1-x-yz=1+y+z-2-yz=(y-1)+z(1-y)= (y-1)(1-z) . Applying the same substitution to -y and -z yields 1-y-xz= (x-1)(1-z) and 1-z-xy= (x-1)(1-y) .

Hence, \frac{1}{1-x-yz} + \frac{1}{1-y-xz} + \frac{1}{1-z-xy} ={frac{1}{(y-1)(1-z)} + \frac{1}{(x-1)(1-z)} + \frac{1}{(x-1)(1-y)}=\frac{a}{b}.

(\frac{1}{1-z}) (\frac{1}{y-1} + \frac{1}{x-1})+ \frac{1}{(x-1)(1-y)}=\frac{a}{b} (\frac{1}{1-z}) (\frac{x+y-2}{(x-1)(y-1)})+ \frac{1}{(x-1)(1-y)}=\frac{a}{b} (\frac{1}{1-z}) (\frac{-z}{(x-1)(y-1)})+ \frac{1}{(x-1)(1-y)}=\frac{a}{b} (\frac{1}{(x-1)(1-y)})((\frac{-z}{1-z}) -1)= \frac{a}{b} \frac{1}{(x-1)(1-y)(1-z)}=\frac{a}{b}

But (x-1)(1-y)(1-z) = xyz-yz-xz-xy+x+y+z-1= (4)-(3)+(2)-1=2 , then \frac{1}{(x-1)(1-y)(1-z)}=\frac{a}{b}=\frac{1}{2}.

Therefore, a+b=1+2= 3

Omkar Krishna
May 20, 2014

From the equation x+y+z=3, 1-x=y+z-1.

Now 1-x-yz =y+z-1-yz =y(1-z)-1(1-z) =(y-1)(1-z)

Hence 1/(1-x-yz) = 1/((y-1)(1-z))

Similarly 1/(1-y-zx) = 1/((z-1)(1-x)) and 1/(1-z-xy) = 1/((x-1)(1-y))

(1/((y-1)(1-z)))+ (1/((z-1)(1-x))) = 1/(z-1)(1/(1-x)-1/(y-1)) =(x+y-2)/((z-1)(1-x)(y-1))

(x+y-2)/((z-1)(1-x)(y-1))+1/((x-1)(1-y)) = 1/(1-x)(y-1) ((x+y-2)/(z-1)+1) = (x+y+z-3)/((1-x)(y-1)(z-1)) = (2-3)/((1-x)(y-1)(z-1)) = 1/((x-1)(y-1)(z-1)) = 1/((xy+1-x-y)(z-1)) = 1/(xyz-(xy+xz+yz)+(x+y+z)-1) = 1/(4-3+2-1) = 1/2

"From the equation x+y+z=3, 1-x=y+z-1." Here x+y+z=2 was meant instead

Calvin Lin Staff - 7 years ago
Si Yu How
May 20, 2014

plus all fraction to get a fraction and use fundamental theorem of symmetric polynomial to put it into rational polynomial of x+y+z, xy+yz+zx and xyz.

Calvin Lin Staff
May 13, 2014

Observe that since x = 2 y z x=2-y-z , so 1 x y z = 1 ( 2 y z ) y z = 1 + y + z y z = ( y 1 ) ( z 1 ) 1-x-yz = 1 - (2-y-z) - yz = -1 +y + z - yz = -(y-1)(z-1) . We have similar expressions for the other two denominators, so this motivates using the substitution a = x 1 , b = y 1 , c = z 1 a = x-1, b=y-1, c=z-1 , and we wish to calculate 1 b c 1 c a 1 a b = a + b + c a b c - \frac {1}{bc} - \frac {1}{ca} - \frac {1}{ab} = - \frac {a+b+c}{abc} .

Since x , y , z x, y, z are roots to the cubic polynomial M 3 2 M 2 + 3 M 4 M^3 - 2M^2 + 3M - 4 , we use the substitution N + 1 = M N+1=M to get that a , b , c a, b, c are roots to the cubic polynomial ( N + 1 ) 3 2 ( N + 1 ) 2 + 3 ( N + 1 ) 4 = N 3 + N 2 + 2 N 2 (N+1)^3-2(N+1)^2+3(N+1)-4 = N^3 +N^2 +2N -2 . Hence, by Vieta's formula, a + b + c a b c = 1 1 2 1 = 1 2 -\frac {a+b+c}{abc} = -\frac { -\frac {1}{1} } {-\frac {-2}{1} } = \frac {1}{2} . Hence, a + b = 3 a+b =3 .

Aman Rajput
May 20, 2014

using three given conditions , we obtain x^2 + y^2 + z^2 = -2 this implies that there must be two conjugate pairs in x ,y and z ley y and z be conjugate pairs from the new condition , we get x^3 - 2x^2 + 3x - 4 =0 solving it we get x=1.65063

putiing x in given three equations you will get y=0.174 - 1.54i z=0.174 + 1.54i

hence , [1/( 1−x−yz) +1 /(1−y−zx) +1/( 1−z−xy ) ] = 1/2

thus , 1 + 2 = 3 is the required answer.

One cannot get a precise answer by approximate computer calculations

Calvin Lin Staff - 7 years ago
Attain k Gupta
May 20, 2014

The solution is impossible to understand. It seems like it was copied from somewhere (possibly, student's own work) without double-checking that it copied correctly. Parts seem to be simply missing.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...